2022
DOI: 10.1038/s41598-022-21013-w
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of calcium phosphate does not further improve in vitro and in vivo osteogenesis in a novel, highly biocompatible, mechanically stable and 3D printable polymer

Abstract: At a time of unpredictable challenges for health, one trend is certain: there is an exceedingly high demand for functional implants, particularly bone grafts. This has encouraged the emergence of bone tissue engineering substitutes as an alternative method to conventional bone grafts. However, the current approaches in the field face several limitations that have prevented the ultimate translation into clinical settings. As a result, many attempts have been made to fabricate synthetic bone implants that can of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The Si 3 N 4 /3wt% MWCNT substrate was appropriately biocompatible and the caCP addition to the biopolymer matrix noticeably advanced the cell attachment. The obtained results here agree well with other research works, in which the amorphous CaP particles and different composites were studied and characterized concerning their boosted osteogenic level [57][58][59][60][61][62][63].…”
Section: Cell Concentration On Samples and Lactate Dehydrogenase (Ldh...supporting
confidence: 91%
“…The Si 3 N 4 /3wt% MWCNT substrate was appropriately biocompatible and the caCP addition to the biopolymer matrix noticeably advanced the cell attachment. The obtained results here agree well with other research works, in which the amorphous CaP particles and different composites were studied and characterized concerning their boosted osteogenic level [57][58][59][60][61][62][63].…”
Section: Cell Concentration On Samples and Lactate Dehydrogenase (Ldh...supporting
confidence: 91%
“…The combination of PLGA and poly(isosorbide sebacate) (PISEB) was shown to be cytocompatible with HUVEC and showed pro-angiogenic gene expression [ 28 ]. Moreover, CSMA-2 demonstrated an angiogenic response that can be observed via CAM assay and IHC analysis of CD-31 markers, with or without calcium phosphate addition [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isosorbide can serve as the backbone for polymers with methacrylate or acrylate groups as the functional groups [ 3 ]. Several studies have demonstrated successful 3D printing with various isosorbide-based composites for hard tissue engineering [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different from those of the OPN and OCN, the RUNX2 gene expressions in our result were not affected by the HA percentage on the scaffold. The presence of aliphatic side chains and cyclohexenes on the CSMA-2 that increased the surface charge of the 3D-printed scaffold might be able to promote differentiation without the help of HA [ 52 ]. Furthermore, the metabolic activity was significantly lower in the CSMA-2 scaffolds incubated with the osteogenic medium ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%